CAM-Type Impingement in the Ankle - Amendola, Ned (The University of Iowa, 2012)
BACKGROUND: Anterior ankle impingement with and without ankle osteoarthritis (OA) is a common condition. Bony impingement between the distal tibia and talus aggravated by dorsiflexion has been well described. The etiology of these impingement lesions remains controversial. This study describes a cam-type impingement of the ankle, in which the sagittal contour of the talar dome is a non-circular arc, causing pathologic contact with the anterior aspect of the tibial plafond during dorsiflexion, leading to abnormal ankle joint mechanics by limiting dorsiflexion. METHODS: A group of 269 consecutive adult patients from the University of Iowa Hospitals and Clinics who were treated for anterior bony impingement syndrome were evaluated as the study population. As a control group, 41 patients without any evidence of impingement or arthrosis were evaluated. Standardized standing lateral ankle radiographs were evaluated to determine the contour of the head/neck relationship in the talus. Two investigators made all the radiographic measurements and intra- and inter-observer reliability were measured. RESULTS: 34% of patients were found to have some anterior extension of the talar dome creating a loss of the normal concavity at the dorsal medial talar neck. A group of 36 patients (13%) were identified as having the most severe cam deformity in order to assess any correlation with coexisting radiographic abnormalities. In these patients, a cavo-varus foot type was more commonly observed. Comparison with a control group showed much lower rates of anterior-medial cam-type deformity of the talus. CONCLUSIONS: Cam type impingement of the ankle is likely a distinct form of bony impingement of the ankle secondary to a morphological talar bony abnormality. Based on the findings of this study, this form of impingement may be related to a cavovarus foot type. In addition, there may be long term implications in the development of ankle OA. LEVEL OF EVIDENCE: Level III